Biochemical Composition of the Ovary of Mystus Nemurus (Cuvier and Valenciennes) and Influence of Ascorbic Acid Supplementation on the Egg and Larval Quality - G. Sebastian Somga, Sonia (1996)
Selected biochemical compositions of the ovaries such as proximate composition, amino acid, fatty acid and ascorbic acid were determined and their role in developing eggs and larvae were evaluated. The ovaries contained substantial amounts of protein, lipid, and ascorbic acid. The protein comprised of high levels of both essential and non essential amino acids, while, the lipid cons is ted of higher proportions of saturated and monounsaturated fatty acids, and lower proportion of polyunsaturated fatty acid (PUFA), respectively. These biochemical components did not show any significant (p> 0.05) changes at different gonad somatic index levels. Al though histology revealed that ovaries demonstrated asynchronous oocyte development, it appeared that there is continuous accumulation of nutrients into the oocyte until final maturation stage. eggs and larvae, marked reduction in protein, lipid, essential amino acid, saturated fatty acid and ascorbic acid contents indicated endogenous utilization. Quantitative decrease of these constituents suggested that more nutrients were utilized during embryonic development.